“I bless you, God who heals you”: an analysis of the resistance of the mourners in the culture of the city of Fagundes-PB (Research, Society and Development, 2022)
The present work has as its main objective, to start a reflection on the culture of the mourners, very striking in the Northeast region, especially in the city of Fagundes - PB. We will bring here aspects that will start from the very origin of the Brazilian population, contemplating the historical context of the construction of female knowledge and the respective mystical atmosphere that involves this knowledge - especially in the Middle Ages - until the use of this knowledge as a support to the methods advances in modern medicine. This work was elaborated through the method of bibliographical research in an exploratory way with a qualitative approach, which was used several sources, such as: online access to books and articles on the subject in question Throughout the discussion and results that is involved through of a singular concern, we can observe the symbiotic relationship between this knowledge built on the basis of the woman's relationship with nature and aspects related to faith, which bring with them references from different religious matrices, which, here in Brazil, Began to form , based on this relationship, a complex range of other relationships, which appear secondarily. In this way, a perspective of continuity of this form of cultural expression is identified, but that this continuity tends to decrease over the years, the new generation does not seek prayer as an instrument for healing and resolving illnesses. It can also be observed that this practice has been decreasing with the advancement of medical sciences and that access to medicines today is easier. It is concluded that, the rezadeiras are considered as a family and religious cultural figure, aimed at solving everyday problems, and they see their craft as a gift, in which God, but which is passed on by generation, and, the new generations do not seek to acquire this knowledge.